COMPETITIVE INTELLIGENCE AND MARKETING EFFECTIVENESS OF ORGANIZATIONS: AN INVESTIGATION FROM PAKISTAN - Ahmed, Rizwan Raheem; Ahmad, Nawaz; Khoso, Imamuddin; Arif, Khawaja A.; Palwishah, Rana I. (European Scientific Journal, ESJ, 2014)
This study examines, how the Competitive intelligence is important to make the marketing effective for a business. Competitive intelligence is a phenomenon in the business world that has started gaining more importance and attention. Competitive intelligence is the both external and internal information of the environment in which a business operates. Competitive intelligence is a tool through which business can gain competitive advantage and compete against their competition. In this research competitive intelligence is diffused into sub variables which all combine to make competitive intelligence. The sub variables include market opportunities, competitor risks, competitor threats, technological intelligence, technical intelligence, and strategic intelligence. Through this research it tested whether competitive intelligence is being used by the organizations in Pakistan which will prove the importance of competitive intelligence in business and it is also shown to what extent it is used. T-test has been used to individually test each variable and see for significance. The results of the research show that all the sub variables are significantly used by the organizations in Pakistan to make their marketing effective and thus competitive intelligence is important to make the marketing effective for a business.